Digital holography to light field - Zuo, Chao (2014)
Holography uses wave (physical) optical principles of interference and diffraction to record and display images. Interference allows us to record the amplitude and phase of the optical wave emanating from an object on a film or recording medium and diffraction enables us to see this wave-field, i.e. the amplitude and phase of the object. Visually this corresponds to both perspective and depth information being reconstructed as in the original scene. Digital Holography has enabled quantification of phase which in some applications provides meaningful engineering parameters. There is growing interest in reconstructing this wavefield without interference. Thus the non-interferometric Transport of Intensity Equation (TIE) method is gaining increased research, which uses two or more defocused images to reconstruct the phase. Due to its non-interferometric nature, TIE relaxes the stringent beam-coherence requirements for interferometry, extending its applications to various optical fields with arbitrary spatial and temporal coherence. The alternate school of thought emerges from the computer science community primarily deals with ray optics. In a normal imaging system all rays emerging from an object point into are focused to a conjugate image point. Information of ray direction is lost and thus the perspective and depth information. A light field image is one that has information of both amplitude and direction of rays fanning from any object point and thus provides perspective (or what could be termed as phase) of the object wave as well. It would thus be possible to extract phase as we know it from this albeit for a coherent illumination case.